2018
DOI: 10.1038/s41598-018-24709-0
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Signature in Human Melanoma Cell Lines from Different Disease Stages

Abstract: Cancer cells rewire metabolism to sustain high proliferation rates. Beside glycolysis and glutaminolysis, amino acids substitute as energy source, feed fatty acid biosynthesis and represent part of the secretome of transformed cells, including melanoma. We have therefore investigated acetate, pyruvate and the amino acid composition of the secretome of human melanoma cells representing the early slow (WM35, WM278, WM793b and VM21) and metastatic fast (A375, 518a2, 6F and WM8) growth phase in order to identify p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 39 publications
(63 reference statements)
2
9
0
1
Order By: Relevance
“…We first examined melanoma cell GH signaling in the human WM35 cell line, which was established from a primary superficial spreading melanoma in radial/vertical growth phase [22]. Cells were treated with GH (500 ng/mL) for 0, 2, 5, 10, 15, 30 or 60min.…”
Section: Resultsmentioning
confidence: 99%
“…We first examined melanoma cell GH signaling in the human WM35 cell line, which was established from a primary superficial spreading melanoma in radial/vertical growth phase [22]. Cells were treated with GH (500 ng/mL) for 0, 2, 5, 10, 15, 30 or 60min.…”
Section: Resultsmentioning
confidence: 99%
“…Metabolic heterogeneity between melanoma subtypes was also reflected by significant alterations in beta-alanine, alanine, aspartate, glutamate, as well as histidine metabolism. In a previous study, altered glutamate and alanine levels were identified as the main differences in conditioned media of cell cultures of early-stage non-metastatic and metastatic melanoma cells, indicating a stage-specific requirement for glutamate and alanine for growth and aggressiveness [ 78 ]. Changes in alanine, aspartate, glutamate, as well as beta-alanine metabolism were recently associated with melanoma development [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor cells release Glu mainly via the xc− antiporter, a transporter that plays a critical role in maintaining intracellular and extracellular antioxidant levels (e.g., glutathione, cysteine) by exchanging extracellular cystine for intracellular glutamate 6 , 63 . Excess extracellular Glu has been shown to enhance glioma and melanoma tumor cell growth and invasion 1 , 63 – 66 , and studies have demonstrated that inhibiting the release of Glu results in a decrease of melanoma tumor growth in mGlu1 receptor-expressing melanomas 63 , 67 . Similarly, our results demonstrate that reducing extracellular Glu levels following BGS treatment inhibits tumor cell proliferation and induces apoptotic tumor cell death.…”
Section: Discussionmentioning
confidence: 99%